STUDI KOMPARASI SEWA MENYEWA RAHIM ANTARA NEGARA INDIA DAN THAILAND DENGAN HUKUM DI INDONESIA DALAM ASPEK HUKUM PERDATA - Amaris Arin Aprilia (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to assess the legal issue of surrogacy in the scope of Indonesian private law, along with a comparison with Indian and Thai domestic laws concerning related matters. This article applies the method of juridical normative, with analytical and descriptive character. The legal data provided in this article contains both primary and secondary data. The data collection technique is library based, including the use of digital libraries. Data collection begins with research, and the information collected will be analyzed deductively with the method of syllogism. The results of this research indicate that infertility is the main driving factor for surrogacy as a form of last-resort alternative to have a baby. Surrogacy starts with agreements between the subject and works almost similarly with In Vitro Fertilization (IVF), but the embryo is implanted into someone else's womb. The absence of support for surrogacy agreements within the Indonesian health regulations make the existing agreements invalid in the eyes of the law because they violate one of the legal terms of the agreement according to the Civil Code. India and Thailand initially permitted commercial surrogacy. However, the increasing number of abandonment cases from surrogacy led to the two countries into banning commercial surrogacy and later requiring certain conditions for voluntary actions.